2018
DOI: 10.1016/j.jcv.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Using a novel rapid viral test to improve triage of emergency department patients with acute respiratory illness during flu season

Abstract: Rapid POC-PCR for influenza and RSV in ED triage has excellent sensitivity and specificity and the potential to improve social distancing practices through better triage and increase appropriate prescription of antimicrobials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…27,28 For influenza virus, and in some cases RSV, studies utilizing point-of-care (POC) diagnostic tests for these specific organisms have shown value in terms of patient management, patient cohorting and droplet precautions, and appropriate anti-viral therapy. [29][30][31] However, for large, molecular multiplex methods, it is unclear whether or not they should be employed broadly for general surveillance purposes, or restricted to specific populations, i.e., pediatric patients, high risk ED patients, and the immunocompromised. 27 Coinfections are more readily detected on molecular panels, however, clinical consequences of coinfections are not totally clear.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 For influenza virus, and in some cases RSV, studies utilizing point-of-care (POC) diagnostic tests for these specific organisms have shown value in terms of patient management, patient cohorting and droplet precautions, and appropriate anti-viral therapy. [29][30][31] However, for large, molecular multiplex methods, it is unclear whether or not they should be employed broadly for general surveillance purposes, or restricted to specific populations, i.e., pediatric patients, high risk ED patients, and the immunocompromised. 27 Coinfections are more readily detected on molecular panels, however, clinical consequences of coinfections are not totally clear.…”
Section: Resultsmentioning
confidence: 99%
“…The study that reported the lower sensitivity might have been subject to bias because only negative results were systematically centrally controlled, thus increasing the likelihood of false positives. Only one study investigated the performance of RT-PCR assay at triage [11] and found a sensitivity and specificity of respectively 1.00 and 0.95. However, this result is based on only 38 specimens obtained during a normal working day.…”
Section: Discussionmentioning
confidence: 99%
“…[8,10] Evaluation of the patient’s viral-status is important to determine if the patient requires isolation or not, and thus to ensure the smooth running of the emergency department and hospitalization units. [11]…”
Section: Introductionmentioning
confidence: 99%
“…For example, antiviral drugs may be started more quickly and appropriately and unnecessary antibiotics stopped earlier [ 4–8 ]. Additionally, rapid diagnosis may offer the potential to decrease transmission to other patients and staff by rapid instigation of relevant infection prevention and control precautions [ 7, 9, 10 ], and may assist clinicians to make decisions earlier regarding discharge of infected patients, potentially reducing their length of stay in hospital and easing pressure on hospital beds [ 11 ].…”
Section: Introductionmentioning
confidence: 99%